A Common Coordinates/Heading Direction Generation Method for a Robot Swarm with Only RSSI-Based Ranging. (25th March 2009) - Hara, Shinsuke; Ishimoto, Tatsuya; Kitano, Masaya; Tsujioka, Tetsuo
Abstract : In the motion control of a microrobot swarm, a key issue is how to autonomously generate a set of common coordinates among all robots and how to notify each robot of its heading direction in the generated common coordinates without any special devices for estimating location and bearing. This paper proposes a set of common coordinates and a heading direction generation method for a robot swarm with only received signal strength indicator (RSSI) measured through wireless communications. We explain the principle of the proposed method and show some computer simulation results on the location and direction estimation errors. Finally, we demonstrate some experimental results using a swarm composed of five robots with the IEEE 802.15.4 standard as its wireless communication tool.